The effects of the decentralization of collective bargaining on wages and wage dispersion: Evidence from the Finnish forest and IT industries - Antti Kauhanen (The Research Institute of the Finnish Economy (ETLA), 2023)
Recently, Finnish forest industries shifted from sectoral collective bargaining to firm-level bargaining, and the IT services industry shifted to a hybrid of sector- and firm-level bargaining. Using administrative data on monthly wages and the synthetic difference-in-differences method, I study the causal effects of collective bargaining decentralization on the level and dispersion of wages. Despite the substantial change in the level of collective bargaining, I generally find muted effects on the level and dispersion of wages. I find positive and economically and statistically significant effects on wage levels and within-firm wage dispersion only for blue-collar workers in the paper industry. The results are, in many respects, similar to those reported previously, especially by studies using credible designs. A possible explanation for the modest changes in the level and dispersion of wages is that employers still face fairly strong unions. Unions also have substantial bargaining power locally, which limits the scope of changes due to bargaining decentralization. It should also be noted that these results are short-term results and long-term results may be different.
Keywords: J31; J52; J53; 330; Collective bargaining; Decentralization; Local bargaining; Wage dispersion